Epidermal growth factor receptor signaling and the progression of diabetic nephropathy. Issue 5 (8th January 2015) - Koya, Daisuke
<x xml:space="preserve">Abstract</x> The current understanding based on a series of EGFR research studies may shed light on a potential therapeutic implication of EGFR inhibition in diabetic nephropathy. <boxed-text content-type="graphic" id="jdi12317-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>